2009
DOI: 10.1007/s00167-008-0705-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of the distal biceps brachii tendon: clinical and isokinetic long-term follow-up

Abstract: Anatomical reinsertion of the avulsed distal biceps tendon is the recommended treatment, but the results are hampered by complications. The purpose of this study is to show the results of patients surgically treated with a non-anatomical reinsertion of this tendon. From 1972 to 2006, 26 non-professional athletic patients were surgically treated by suture of the tendon on the brachialis muscle tendon. At follow-up 23/26 patients underwent clinical and isokinetic evaluation. At a medium follow-up of 84 months, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…3,4,9,11,12,16,24,26,30,32,34,37,40,41,43,44 One study found that peak supination torque occurred at 12 of forearm supination during isokinetic testing of a normal population, leading us to believe that the peak strength measurements in the literature might not be representative of the entire function of the repair. 16 Isokinetic testing does not typically involve comparisons of peak supination strength differences at different forearm positions, other than positions of maximum torque.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…3,4,9,11,12,16,24,26,30,32,34,37,40,41,43,44 One study found that peak supination torque occurred at 12 of forearm supination during isokinetic testing of a normal population, leading us to believe that the peak strength measurements in the literature might not be representative of the entire function of the repair. 16 Isokinetic testing does not typically involve comparisons of peak supination strength differences at different forearm positions, other than positions of maximum torque.…”
Section: Discussionmentioning
confidence: 93%
“…3,24,34,38 While some controversy continues to exist over the need for repair of an acute distal biceps tendon, surgical repair has been shown to be a better alternative in patients with higher physical activity than nonoperative treatment for restoration of strength and endurance. 3,8,12,15,24 Current surgical methods have focused on approaches to the biceps tuberosity and initial attachment strength. 2,5,13,20,27,28,38 There are numerous in vitro biomechanical studies discussing attachment of the tendon either with sutures, suture anchors, interference screws, or a cortical button.…”
mentioning
confidence: 99%
“…Early detection and therapy of the distal biceps tendon brachii is crucial for obtaining the best clinical and functional outcomes [8]. Several treatment options, including operative or non‐operative treatment procedures, have been described in the literature [1, 2, 8, 10, 13, 23, 25, 26]. Previous studies have shown that conservative treatment can result in loss of flection and supination strength as well as decreased patient satisfaction [2, 8, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, the non-anatomical surgery consists in the tenodesis of the ruptured distal biceps on the anterior brachialis muscle tendon, altering the native biomechanics of the forearm. Through the years the non-anatomical approach has been gradually abandoned, although satisfactory results obtained using this technique were reported (8,23). Different fixation devices can assist in the anatomical reinsertion: suture anchors (24), interference screws (16) or suspension devices (25).…”
Section: Discussionmentioning
confidence: 99%